PROGRAM AND TECHNICAL COMPLEX OF IMPLEMENTATION OF THE INFORMATION SYSTEM OF DIAGNOSTICS OF THE TECHNICAL CONDITION OF BUILDINGS - Терентьєв, Олександр; Горбатюк, Євгеній; Тисленко, Олександр; Биков, Вадим (SWorldJournal, 2025)
The relevance of the research is due to the problem of research and development of information technology and analytical tools for its support for the automated diagnosis of technical condition of building structures and structures at the stages of their